2009
DOI: 10.1111/j.1600-0609.2008.01189.x
|View full text |Cite
|
Sign up to set email alerts
|

Combination of DNA methylation inhibitor 5‐azacytidine and arsenic trioxide has synergistic activity in myeloma

Abstract: XAF1 is a newly identified candidate tumour-suppressor gene that can antagonise XIAP and sensitise cells to cell death triggers. This study was undertaken to study the effect of 5-azacytidine (AZA) on XAF1 expression in myeloma cells and efficacy of 5-AZA and arsenic trioxide (ATO) combination treatment in myeloma in vivo and in vitro. XAF1 expression was analysed by semi-quantitative PCR and western blotting. Methylation specific PCR was used to detect methylation status of XAF1 promoter CpG islands. RPMI 822… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…Tong and Fu et al [10,11] found reexpression of p15 and p16 through the demethylation of their promoters in the U266 and MUTZ-1 cell lines, respectively. In addition, a previous study found that arsenic trioxide combined with the demethylation drug azacitidine showed increased demethylation in in vivo and in vitro experiments [12]. The above results suggest that the combination of arsenic trioxide and decitabine may have a similar effect.…”
Section: Introductionmentioning
confidence: 56%
“…Tong and Fu et al [10,11] found reexpression of p15 and p16 through the demethylation of their promoters in the U266 and MUTZ-1 cell lines, respectively. In addition, a previous study found that arsenic trioxide combined with the demethylation drug azacitidine showed increased demethylation in in vivo and in vitro experiments [12]. The above results suggest that the combination of arsenic trioxide and decitabine may have a similar effect.…”
Section: Introductionmentioning
confidence: 56%
“…In this regard, it is noteworthy that TRAIL, a TNF superfamily member, ligates two types of receptors: death receptors triggering TRAIL-induced apoptosis (TRAIL R1 and TRAIL R2) and decoy receptors that act as sinks for TRAIL and administering ATO to MM patients. More studies showed a synergic effect when ATO is administered in combination with other anti-MM drugs, such as bortezomib, the DNA methylation inhibitor 5-azacytidine and melphalan et al [31][32][33][34] The findings in this study offer a promising and novel strategy, using ATO to activate TRAIL, in the treatment of myelomas, especially those aggressive myeloma subtypes with low expression of TRAIL, such as MS subgroup with reciprocal translocation (4:14) and MF subgroup with reciprocal translocations (14:16) and (14:20).…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13] With the exception of one recent study, 14 the epigenetic factors contributing to the pathogenesis of myeloma have been studied on a gene-by-gene basis and, with the use of methylation-specific PCR, several genes have been identified that are hypermethylated, including VHL, XAF1, IRF8, TP53, CDKN2A, CDKN2B, DAPK, SOCS1, CDH1, PTGS2, CCND2, and DCC. [15][16][17][18][19][20][21][22] Promoter hypermethylation of cyclin-dependent kinase inhibitor 2A (CDKN2A) and TGFBR2 have been shown to correlate with poor prognosis in myeloma patients, although the prognostic value of CDKN2A hypermethylation remains debatable. 16,23,24 In this study we used the Infinium array (Illumina) to analyze CpG island promoter methylation with normal PCs, MGUS, myeloma, and PCL samples to identify methylation changes that may contribute to the pathogenesis of myeloma or that could act as prognostic factors.…”
Section: Introductionmentioning
confidence: 99%